Results of food import substitution in Russia - M. Yarkova, Tatyana (2019)
Import substitution processes which are the focus of Russia's agricultural and food policy, are conditioned and strengthened mostly due to the sanctions of the United States and other Western countries. Importance of import substitution, rather than a change of importers, is reflected not only in scientific works of research economists, but also in regulatory documents, the development of which has become active in Russia since 2010. During the past eight years, import substitution policy in the Russian Federation has obtained significant positive results. In particular, a decrease in the share of imports in commodity resources was revealed for all commodity groups of basic foodstuffs. Possible threshold values for the share of imports have been exceeded in such commodity groups as beef meat, including by-products, as well as cheeses, milk and cream. At the same time, the level of food supply and self-sufficiency is not fulfilled for such types of food as milk and vegetables. To implement all the import substitution targets, it is necessary to minimize the impact of a number of negative internal and external factors that significantly affect the agricultural production industry. Along with this, it is important to implement the policy concerning the domestic system of provision and supply food with a view to their even distribution within the regions.